The Climate Change Challenge and Barriers to the Exercise of Foresight Intelligence. (13th April 2016) - Ross, Lee; Arrow, Kenneth; Cialdini, Robert; Diamond-Smith, Nadia; Diamond, Joan; Dunne, Jennifer; Feldman, Marcus; Horn, Robert; Kennedy, Donald; Murphy, Craig; Pirages, Dennis; Smith, Kirk; et al.
Abstract: Despite solid evidence from the scientific community about climate disruption, much of the US public remains unconvinced about the reality of anthropogenic change, and national governments have been slow to undertake major steps to deal with the climate crisis. In order to understand this lack of foresight intelligence regarding climate disruption, we identify some features of climate disruption and human psychology that combine to create barriers to effective action. We also review encouraging, albeit modest, successes in persuading Americans to conserve energy through "psych-wise" initiatives. Although the reductions in energy consumption accomplished by these initiatives and strategies fall far short of what is required to address impending global climate change, we believe that the principles underlying these initiatives suggest ways to achieve more substantial reductions. We conclude by offering some specific steps that could be taken to achieve such reductions and more generally meet the building global challenge.